Assessing Uzbekistan’s Transition : Country Economic Memorandum - Izvorski, Ivailo; Vatyan, Arman; Trushin, Eskender; Abdul-Hamid, Husein; Dalvit, Nicolo; Safarov, Maksudjon; Iootty, Mariana; Novikova, Marina; Melecky, Martin; Ahmedov, Mohirjon; Manuilova, Natalia; Zorya, Sergiy; et al. (World Bank, Washington, DC, 2021)
Uzbekistan’s transition from planning to market started almost thirty years ago following its independence from the Soviet Union. For most of this period, economic modernization and transformation were stalled, with little change in institutions and policies from those prevailing at the time of the planned economy. In late 2016, Uzbekistan surprised by launching reforms with a breadth and speed that at times exceeded the pace of those observed in some of the earlier reformers at a similar stage of the process. In November 2018, building on the results from more than a year of economic reforms, the government announced the agenda for the next phase of its bold and ambitious economic transformation. In terms of the pace of transition, Uzbekistan’s record has been mixed but appropriate, given that reforms are dependent on experience with markets and prices, initial conditions, and institutional strength. Before the Coronavirus (COVID-19) pandemic started, the reform momentum was supported by comfortable external and fiscal buffers and a robust global economy. The buffers are still sizable, even with doubling of public debt since 2017, and a sign of strength but the pull from the global economy has been substantially diminished. The rest of the introduction reviews progress in the key areas of economic transformation.